Participation in Out-of-Home Environments for Young Children With and Without Developmental Disabilities. (July 2016) - Lim, Chun Yi; Law, Mary; Khetani, Mary; Pollock, Nancy; Rosenbaum, Peter
This study examines caregivers' perceptions of participation patterns and environmental supports and barriers for young children with and without developmental disabilities within their child care/preschool and community settings. The Young Children's Participation and Environment Measure (YC-PEM) was completed by 151 parents of Singaporean children (0-7 years old) with and without developmental disabilities. Setting-specific summary and item-level scores of these children were compared using ANCOVA, Mann–Whitney U, and Pearson chi-square tests. Children with developmental disabilities had significantly lower participation and environment summary scores in both settings as compared with children without developmental disabilities ( p < .05;η p 2 = 0.03-0.31). Group differences were also evident at the item level, particularly when comparing the percentage of parents who desire change in their child's activity participation. Adequate financial support, public awareness, programs, and services have been identified as environmental factors that are potentially important to parents of children with developmental disabilities.